Changing patterns in the export of goods versus international competitiveness: A comparative analysis for Central-East European countries in the period 2000-2011 - Ewa Lechman (Comparative Economic Research. Central and Eastern Europe, 2014)
This paper discusses the existing links between changing patterns in the export of goods, broken down by technology-intensity, versus intrenational competitiveness. The study covers nine Central-East European (CEE) economies: Bulgaria, the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Romania and the Slovak Republic, in the time span 2000-2011. We examine the hypothesis of a strong, positive and statistically significant relationship between flows of export of high-tech and ICT manufactures industries goods, and an economy's level of international competitiveness (approximated by the Global Competitiveness Index - GCI, see: World Economic Forum). Our methodological approach relies on elaboration of each country`s individual export patterns with regard to industries of different technology-intensities, and statistical analysis between the international GCI variable and variables identifying shares in total export of certain industries. Contrary to what was initially expected, our empirical results do not seem to support the hypothesis on statistically positive links between growing shares of high-tech and ICT manufactures industries in the total value of export versus the Global Competitiveness Index in the analyzed countries.
Keywords: 330; competitiveness; export; technology-intensity; comparative analysis